Optical coherence tomography and disease subtype in multiple sclerosis - Pulicken, M; Gordon-Lipkin, E; Balcer, L J; Frohman, E; Cutter, G; Calabresi, P A (Neurology, 2007)
To examine retinal nerve fiber layer (RNFL) thickness, macular volumes (MV), and visual acuity in multiple sclerosis (MS) eyes, with and without history of acute optic neuritis (ON). RNFL thickness was measured in 326 MS and 94 control eyes using optical coherence tomography (OCT). MV and vision testing were done in a subset of the cohort. MS subtype was classified as relapsing-remitting (RRMS, n = 135), primary progressive (PPMS, n = 12), and secondary progressive (SPMS, n = 16). MS ON eyes had decreased RNFL thickness (84.2 microm) compared to controls (102.7 microm) (p < 0.0001). Unaffected fellow eyes of MS ON eyes (93.9 microm) (p < 0.01) and patients with MS with no history of ON (95.9 microm) (p < 0.05) also had decreased RNFL. RRMS (94.4 microm) (p < 0.001), PPMS (88.9 microm) (p < 0.01), and SPMS (81.8 microm) (p < 0.0001) (adjusted for age and duration of disease) had decreased RNFL compared to controls. There were significant differences in RNFL thickness within quadrants of peripapillary retina comparing relapsing to progressive MS subtypes. MV was decreased in MS ON eyes (6.2 mm(3)) (p < 0.0001) and SPMS subjects (6.2 mm(3)) (p < 0.05) compared to controls (6.8 mm(3)). Retinal nerve fiber layer (RNFL) is significantly decreased in multiple sclerosis (MS) optic neuritis (ON) eyes, unaffected fellow eyes of patients with MS ON, and MS eyes not affected by ON in our cohort. Macular volumes (MV) showed a significant decrease in MS ON eyes. Progressive MS cases showed more marked decreases in RNFL and MV than relapsing-remitting MS. OCT is a promising tool to detect subclinical changes in RNFL and MV in patients with MS and should be examined in longitudinal studies as a potential biomarker of retinal pathology in MS.